Migration, population mobility and “life spaces” in the Identity Territory of Southwest Bahia - Ana Emilia de Quadros Ferraz (Geopauta)
Movement as a social process is the premise for analyzing migration, population mobility and “life spaces”. In this article, this topic is addressed in the Identity Territory of Southwest Bahia (TISB). We opted for quantitative and qualitative analyzes that were associated with a theoretical framework. The results indicate that there was a decrease in population in most municipalities and an increase in population, especially in Vitória da Conquista. The information reveals different population rhythms across the geographic network. Aspects of migration and population mobility processes construct “life spaces” that, in the movement of the geographic network, break with pre-established municipal borders and requalify the possibilities of analyzing population movement as a social process.